The basic space of a revolutionary parliament: Scaling the Frankfurt Assembly of 1848/49. (November 2019) - Herrmann, Michael; Sieberer, Ulrich
We examine whether there is a basic space in a parliament which grew out of a revolution and had no prior history of parliamentarism: the Frankfurt Assembly of 1848/49. We scale all 299 roll call votes to determine the dimensionality of voting as well as the positions of deputies and their party groups. We find two dimensions of disagreement and show that they can be interpreted in line with historical scholarship as conflict over who should govern (the people or the monarch) and conflict over state borders (inclusion or exclusion of Austria). We find that the party groups line up on the first dimension in ways consistent with historical scholarship on their political inclinations, but we also find wide variation in deputies' positions within and across parties. Moreover, deputies' positions turn out to be polarized on the territorial dimension but not on the government dimension. We conclude that ideological constraint was the primary structuring force in parliamentary voting. Our results underscore the pervasiveness of low dimensionality in parliamentary voting even in the absence of strong parties and agenda control.